The Effect of Productive Financing on Customer Income in an Islamic Economic Perspective on Pegadaian Syariah Panyabungan Mandailing Natal - Lutfiansyah, Irham; Nawawi, Zuhrinal M; Harahap, Muhammad Ikhsan (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2025)
The main objective of this research is to find out whether productive financing has an effect on pegadaian syariah on increasing customer income, especially traders who take financing at pegadaian syariah. Based on data collected from customer respondents Pegadaian Syariah Panyabungan, The research uses quantitative methods by distributing questionnaires to measure the extent of productive financing in increasing customer income. The results showed that productive financing has a significant effect on increasing trader income in an Islamic economic perspective. Customers who receive financing experience an increase in income and business capital, which has positive implications for their welfare. Pegadaian Syariah Panyabungan is considered capable of helping the community, especially in terms of providing business capital without involving usury, in accordance with sharia principles.